WEBOMETRICS ANALYSIS OF STATE AND PRIVATE UNIVERSITY RANKINGS ON IMPROVING QUALITY MANAGEMENT OF HIGHER EDUCATION IN INDONESIA - Qurtubi, Ahmad (Journal of Educational Administration, 2022)
The internet is one of several important information sources and the website is one of the important media used to disseminate or practically disseminate information to a wide audience. For educational institutions, websites play a major role when disseminating research findings, publication results, academic or non-academic achievements, and cultural preservation. And the website is also a reflection of the academic quality of an educational institution or university. This study uses a descriptive qualitative approach with library research methods. Based on this research, the implementation of quality management in tertiary institutions can ensure a better and more advanced institutional transformation. From an academic and scientific point of view, Webometric ranking is a very important and informative assessment. Indonesian higher education website scores based on 4 Webometric indices, namely: (transparency, impact, presence, and excellence) need to be increased, because this is a benchmark for how universities can be competent both domestically and internationally. Webometrics ranking can be a benchmark for quality management of higher education in Indonesia.